Successful popliteal and femoral nerve blocks in a patient with severe Guillain‐Barré syndrome. Issue 2 (12th July 2016) - Shariat, Ali; Vig, Sanjana
Summary: We report the successful use of peripheral nerve blocks for open reduction and internal fixation of a tri‐malleolar ankle fracture in a patient with Guillain‐Barré syndrome (GBS) with severe respiratory insufficiency and bulbar weakness. The patient had no adverse neurological sequelae. Peripheral nerve blocks can be safely administered and should be considered in patients with GBS who are at high risk for complications from general anaesthesia.